Upaya Meningkatkan Kemampuan Melaksanakan Pertolongan Pertama pada Kecelakaan dengan Pendidikan Kesehatan Helmet Removal - Sunarto Sunarto; Addi Mardi Harnanto (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: Head and neck injuries as the etiology of death for road users. then there are efforts to overcome them with protective equipment for the head ie the helmet, the use of the right helmet is expected to reduce the burden of collisions directly to the head. Furthermore, when an accident occurs in a patient who is still wearing a helmet, the helper must understand the technique and how to properly remove the helmet. Purpose this community enganggement is necessary to obtain health education through community service in order to improve their knowledge and skills. Methods: In the implementation using question and answer lecture and demonstration models, with the module learning media. Pre-test and post-test is done by asking questions. Results: An increase in the number of correct answers between before and after health education was given. The average increase in the number of correct answers is between 3 to 4. Conclusion: After health education knowledge and skills increased.